Response to stress and allergen production caused by metal ions (Ni, Cu and Zn) in oregano (Origanum vulgare L.) plants - Kulbat-Warycha, Kamila; Georgiadou, Egli C.; Mańkowska, Dorota; Smolińska, Beata; Fotopoulos, Vasileios; Leszczyńska, Joanna (My University, 2020)
Heavy metals are the cause of one of the most significant biosphere contamination problems worldwide, as they can be highly reactive and toxic according to their oxidation levels. Their toxic effects are correlated with the elevated production of reactive oxygen species (ROS) and oxidative cellular damage occurring in plants. The aim of the present study was the investigation of the effects of three heavy metals (Ni, Cu, Zn) applied to the soil in biochemical defense-related responses and allergen production in the aromatic plant oregano (Origanum vulgare L.) from the Lamiaceae family. The concentrations of the three heavy metals used, were based on the 2002 Regulation of the Polish Ministry of the Environment on Soil Quality Standards [(i) agricultural land (group B): Ni 100 ppm, Ni 210 ppm, Cu 200 ppm, Cu 500 ppm, Zn 720 ppm and (ii) industrial land (group C): Ni 500 ppm, Cu 1000 ppm, Zn 1500 ppm, Zn 3000 ppm]. The investigated plants accumulated heavy metal ions in aerial parts to a variable extent. For plants grown in soil contaminated with Zn, phenotypic representation of the growth and development were strongly limited and dependent on zinc concentration. Phenotypic representation of plants grown in soil contaminated with Ni and Cu were characterized by normal growth, slightly lower or equal to that of the control plants. All tested metals (Ni, Cu, Zn) caused a concentration-dependent decrease in photosynthetic pigments especially in total chlorophyll content. Highest cellular damage levels were observed in plants treated with Cu and Zn. Increasing concentration of these metals (especially Zn) caused a further increase in cellular damage. 3000 ppm Zn caused highest increase in the concentration of proline compared with control plants, suggesting osmotic stress imposition. Treatment with 1000 ppm Cu led to increased concentration of the allergenic protein profilin in relation to control plants by profilin ELISA analysis, while increasing concentrations of Cu and Zn led to a decrease in the concentration of phenolic compounds and total antioxidant capacity. On the basis of these findings, Ni stress in oregano plants appears to be less damaging (in relation to Cu and Zn) and with lower allergenic potential, compared with 1000 ppm Cu. The present study provides novel biochemical insight in the defense and allergenic response of aromatic plants to metal ions present in the rhizosphere; however, more comprehensive research under realistic field conditions is needed to fully decipher this interaction.
Keywords: Allergenic proteins; Profilin; Heavy metal; Oregano